2015
DOI: 10.1245/s10434-015-4616-y
|View full text |Cite
|
Sign up to set email alerts
|

Back to Basics: Traditional Nottingham Grade Mitotic Counts Alone are Significant in Predicting Survival in Invasive Breast Carcinoma

Abstract: First-generation molecular profiling assays for estrogen receptor positive invasive breast carcinomas derive much of their predictive power from quantifying genes of proliferation into a single score. Sometimes overlooked in the profusion of molecular data, the time-tested, mitotic count in the Nottingham combined histological grade is a good single-parameter predictor of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Although many studies have assessed the prognostic value of the mitotic count for invasive breast cancer, the prognostic value of the absolute mitotic count is not commonly studied. The mitotic count is typically analysed as a categorical variable that comprises three classes (low, middle and high) with cut-off values that are based on the modified Bloom and Richardson grading system [43,44]. An exception is the study design of Kronqvist et al [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have assessed the prognostic value of the mitotic count for invasive breast cancer, the prognostic value of the absolute mitotic count is not commonly studied. The mitotic count is typically analysed as a categorical variable that comprises three classes (low, middle and high) with cut-off values that are based on the modified Bloom and Richardson grading system [43,44]. An exception is the study design of Kronqvist et al [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…parameters is that the mitotic figures are easy to analyze in routine histological specimens including biopsy, resected, and cytological specimens. Several studies have reported mitotic count as a reliable prognostic marker of breast cancers [14][15][16][18][19][20] ; however, the reproducibility of mitoses can be affected by the counting method used, as discussed in a previous study. 17 Alternatively, the detection of atypical mitoses is simpler with greater consistency once observers become used to recognizing morphological characteristics of mitoses.…”
Section: An Advantage Of Assessing Mitotic Figures Over Other Prognosticmentioning
confidence: 99%
“…Mirza et al reviewed published literature and found that mitotic index can be a prognostic factor for patients with node‐negative breast cancer followed up for more than 5 years. A recent study has also found that mitotic count in histological sections can be a reliable prognostic marker, comparable to the multigene assay . Despite these observations, no previous study has delineated the morphological details of mitotic figures, including atypical mitoses, and particularly, no studies have further assessed the clinical significance of atypical mitoses in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The literature supporting the use of histopathological parameters to guide the selection of GEPTs has accrued during the past decade . We were the first, to our knowledge, to emphasise the relevance of breast pathology data points with GEPTs and demonstrated that histopathological factors predict up to 67% of the ODx RS when we developed the Magee equations (http://path.upmc.edu/onlineTools/MageeEquations.html), which are able to predict clearly low and clearly high ODx RS categories with high accuracy .…”
Section: Discussionmentioning
confidence: 96%
“…Online or Predict (Predict.nhs.org). In addition, there is a robust literature attesting to the close relationship between first‐generation GEPT such as ODx and histopathological variables …”
Section: Introductionmentioning
confidence: 99%